1988
DOI: 10.1002/eji.1830181134
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD8+ thymocytes develop into CD4 or CD8 single‐positive cells in athymic nude mice*

Abstract: A differentiation pathway from CD4+CD8+ cells to CD4+CD8- or CD4-CD8+ cells was investigated in athymic nude mice. Using fluorescence-activated cell sorter, CD4+CD8+ cells were sorted out from AKR thymocytes (H-2k, Thy-1.1) stained with two monoclonal antibodies against CD4 and CD8 (anti-L3T4 and anti-Ly-2). These CD4+CD8+ AKR thymocytes were injected i.v. into CBA or C3H nude mice (H-2k, Thy-1.2) which had received 650 rads and had been reconstituted with syngeneic nude bone marrow cells. The lymph node cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A possible explanation for the delayed decrease in the CD4+SP cell number after CY treatment is as follows : CY preferentially acts on the DP cells (precursors of the CD4+SP cells (Smith 1987 ;Tamauchi et al 1988)) rather than on the CD4+SP cells themselves and therefore this delayed decrease is a sequel to the profound impairment of the DP cells on Day 2. The behavior of the CD8+SP subset was most intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the delayed decrease in the CD4+SP cell number after CY treatment is as follows : CY preferentially acts on the DP cells (precursors of the CD4+SP cells (Smith 1987 ;Tamauchi et al 1988)) rather than on the CD4+SP cells themselves and therefore this delayed decrease is a sequel to the profound impairment of the DP cells on Day 2. The behavior of the CD8+SP subset was most intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…These doublepositive T cells undergo extensive selection that results in the death of the majority of these cells. The surviving double-positive T cells differentiate into medullary T cells that express either CD4 or CD8 but not both (29,30,32). Functionally mature T cells within the thymus express little (35) or no (6) HSA.…”
mentioning
confidence: 99%
“…Most T cell reconstitution studies so far have concentrated on analysing the reconstitution of T cells after the transfer of BM HSC into irradiated hosts ; furthermore, adoptive transfer of cells isolated from fetal liver or neonatal spleen , committed T cell progenitors , double‐positive thymocytes , isolated thymocytes and in‐vitro‐ generated T cell precursors (reviewed in ) have also been studied. Here, we have shown that with a single, simple i.p.…”
Section: Discussionmentioning
confidence: 99%
“…between 3 and 5 weeks of age for best results. Based on technical considerations (accessibility of donor tissue, required cell numbers, route of administration) and the scarcity of studies investigating adoptive transfer of thymocytes , we decided that the i.p. thymocyte transfer was the simplest and most promising method to be tested further.…”
Section: Introductionmentioning
confidence: 99%